2007
DOI: 10.1007/s11010-007-9445-2
|View full text |Cite
|
Sign up to set email alerts
|

Structural remodelling of cardiomyocytes in the border zone of infarcted rabbit heart

Abstract: Cardiomyocyte dedifferentiation, as detected in hibernating myocardium of chronic ischemic patients, is one of the characteristics seen at the border of myocardial infarcts in small and large animals. Our objectives were to study in detail the morphological changes occurring at the border zone of a rabbit myocardial infarction and its use as model for hibernating myocardium. Ligation of the left coronary artery (LAD) was performed on rabbit hearts and animals were sacrificed at 2, 4, 8 and 12 weeks postinfarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 23 publications
1
21
1
Order By: Relevance
“…T-system remodeling in failing rodent hearts has been studied extensively, but t-system components as found in human heart failure or in a porcine infarct model (Pinali et al, 2017) have not been identified. In contrast, images of remodeled t-tubules published by others (Driesen et al, 2007) and us (Seidel et al, 2016), including the present study, indicate that t-system remodeling in rabbit resembles the human phenotype. Driesen et al described vacuole-like structures in cardiomyocytes adjacent to the infarct border in rabbit and suggested that “the vacuoles represent plasma membrane invaginations and/or dilatations of t-tubular structures.” Based on our three-dimensional reconstructions (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…T-system remodeling in failing rodent hearts has been studied extensively, but t-system components as found in human heart failure or in a porcine infarct model (Pinali et al, 2017) have not been identified. In contrast, images of remodeled t-tubules published by others (Driesen et al, 2007) and us (Seidel et al, 2016), including the present study, indicate that t-system remodeling in rabbit resembles the human phenotype. Driesen et al described vacuole-like structures in cardiomyocytes adjacent to the infarct border in rabbit and suggested that “the vacuoles represent plasma membrane invaginations and/or dilatations of t-tubular structures.” Based on our three-dimensional reconstructions (Fig.…”
Section: Discussioncontrasting
confidence: 81%
“…HF has been shown to be accompanied by cardiomyocyte dedifferentiation and a reactivation of the fetal gene programme 39 . Therefore, the structural remodelling observed may also reflect a return to a more ‘fetal phenotype’.…”
Section: Discussionmentioning
confidence: 99%
“…Dedifferentiated myocytes flatten and spread out in culture [45], [46]; sarcomeres become ill-defined and disorganized, and the expression of contractile proteins is dramatically altered [47], [48]. Phenomena akin to in vitro dedifferentiation have also been described in vivo , in fibrillating atria [49], in chronically-ischemic myocardium, and in the border zone of myocardial infarcts [50]. Such dedifferentiated myocytes are not apoptotic and presumably reflect adaptations to abnormal myocardial stress and/or perfusion [51].…”
Section: Discussionmentioning
confidence: 99%